Antigenic Composition of Single Nano-Sized Extracellular Blood Vesicles - Arakelyan, Anush (Nanomedicine, 2014)
Extracellular vesicles (EVs) are important in normal physiology and are altered in various pathologies. EVs produced by different cells are antigenically different. Since the majority of EVs are too small for routine flow cytometry, EV composition is studied predominantly in bulk, thus not addressing their antigenic heterogeneity. Here, we describe a nanoparticle-based technique for analyzing antigens on single nano-sized EVs. The technique consists of immuno-capturing of EVs with 15-nm magnetic nanoparticles, staining captured EVs with antibodies against their antigens, and separating them from unbound EVs and free antibodies in a magnetic field, followed by flow analysis. This technique allows us to characterize EVs populations according to their antigenic distribution, including minor EV fractions. We demonstrated that the individual blood EVs carry different sets of antigens, none being ubiquitous, and quantified their distribution. The physiological significance of antigenically different EVs and their correlation with different pathologies can now be directly addressed.